A systematic review and meta-analysis of the safety and efficacy of left atrial substrate modification in atrial fibrillation patients with low voltage areas - Mao, Shaobin; Fan, Hongxuan; Wang, Leigang; Wang, Yongle; Wang, Xun; Zhao, Jianqi; Yu, Bing; Zhang, Yao; Zhang, Wenjing; Liang, Bin (Frontiers in Cardiovascular Medicine, 2022)
Background The left atrial low-voltage areas (LVAs) are associated with atrial fibrosis; however, it is not clear how the left atrial LVAs affect the recurrence of arrhythmias after catheter ablation, and the efficacy and safety of the left atrial substrate modification based on LVAs as a strategy for catheter ablation of atrial fibrillation (AF) are not evident for AF patients with LVAs. Methods We performed a systematic search to compare the arrhythmia recurrence in AF patients with and without LVAs after conventional ablation and arrhythmia recurrence in LVAs patients after conventional ablation with and without substrate modification based on LVAs. Result A total of 6 studies were included, involving 1,175 patients. The arrhythmia recurrence was higher in LVA patients after conventional ablation (OR: 5.14, 95% CI: [3.11, 8.49]; P < 0.00001). Additional LVAs substrate modification could improve the freedom of arrhythmia in LVAs patients after the first procedure (OR: 0.30, 95% CI: [0.15, 0.62]; P = 0.0009). However, there was no significant difference after multiple procedures (P = 0.19). The procedure time (MD: 26.61, 95% CI [15.79, 37.42]; P < 0.00001) and fluoroscopy time (MD: 6.90, 95% CI [4.34, 9.47]; P < 0.00001) in LVAs patients with additional LVAs substrate modification were significantly increased compared to LVAs patients’ without substrate modification. Nevertheless, there were no higher LVAs substrate modification-related complications (P = 0.93) between LVAs patients with and without additional LVAs substrate modification. In the subgroup analysis, the additional LVAs substrate modification reduced the risk of arrhythmia recurrence in LVAs patients during the follow-up time, which was 12 months (OR: 0.32, 95% CI (0.17, 0.58); P = 0.002), and box isolation (OR: 0.37, 95% CI (0.20, 0.69); P = 0.002) subgroups, but the type of AF, follow up >12 months and homogenization subgroups were not statistically significant. Trial sequential analysis shows conclusive evidence for the LVAs ablation. Conclusion This study has shown that LVAs could improve the risk of arrhythmia recurrence in AF patients after conventional ablation. And additional LVAs substrate modification after conventional ablation could increase the freedom of arrhythmia recurrence in LVAs patients. Interestingly, the box isolation approach appeared more promising. Systematic review registration [http://www.crd.york.ac.uk/prospero], identifier [CRD42021239277].